Removal of textile dye Remazol Brilliant Blue Reactive (RBBR) using fibers of Citrullus lanatus (watermelon) and Cocos nucifera (green coconut) as adsorbent material - Krueger, Melissa Dominique de Sousa; Volkmann, Ana Carolina; Rainert, Karine Thaise (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The accumulation of agro-industrial waste causes major environmental problems since most of these wastes are disposed of improperly. Among them, there are the watermelon (Citrullus lanatus) and the green coconut (Cocos nucifera), fruits of resistant and fibrous peels which are discarded in landfills because they are not widely used. Thus, the adsorption capacity of the Remazol Brilliant Blue Reactive (RBBR) dye was investigated using green coconut and watermelon residues as adsorbents. The combined effects of two independent variables (pH and adsorbent mass) were evaluated using the response surface methodology. Under optimal conditions of acid pH and adsorbent mass of 1 g, the dye removal efficiency reached values above 80% for both residues. The adsorption kinetics was described by the pseudo-second order model, while the equilibrium study was represented by the Freundlich isotherm for the watermelon residue and the Langmuir model for the green coconut. The results show that the agroindustrial residues of watermelon and green coconut could be effectively used to remove dye remazol brilliant blue reactive.